Euglycemic Ketoacidosis in Spinal Muscular Atrophy - Dimitrios Stoimenis; Christina Spyridonidou; Sofia Theofanidou; Nikolaos Petridis; Nikos Papaioannou; Christina Iasonidou; Nikolaos Kapravelos (Hindawi Limited, 2019)
Euglycemic ketoacidosis is defined by the triad of high anion gap acidosis, increased plasma ketones, and the absence of hyperglycemia. Apart from diabetes mellitus, the disorder may occur in prolonged fasting, excessive alcohol consumption, pregnancy, and inborn errors of metabolism. Here, we highlight the diagnosis of euglycemic ketoacidosis in a pediatric nondiabetic patient with spinal muscular atrophy (SMA) type 1 (Werdnig-Hoffmann disease), who, subsequently to her postoperative admission to the intensive care unit following a spinal surgery, developed high anion gap metabolic acidosis. We discuss the pathophysiology of acid-base disorders in SMA, along with the glucose and fatty acids metabolism, the necessary knowledge for medical practitioners.